Combating corruption in India: The role of institutions of governance - Ramulu, Ch. Bala; Narasimha Rao, P. (2011)
The increasing level and magnitude of corruption is often attributed to globalistion of Indian econmy. There is an aprehension that, left unchecked, it can jeopardise the effective functioning of institutions of governance. Though media and civil soceity organisations are trying to draw attention to this growing phenomemnon and have even raised demand for an efficient mechanism to punish the corrupt, yet they can seldom be the substitute to the instituttions of governance. It is the onus of these institutions to formulate policies and implementation of programmes relating to curbing corruption and maintain integrity in administation. Here is an attempt to analyse the functioning of these change agents and suggest measures to stremline and strengthen these institutions. - Reproduced.
Keywords: Corruption - India; Corruption